PREDICTORS OF POSTPARTUM RELAPSES IN WOMEN WITH MULTIPLE SCLEROSIS: RESULTS FROM THE MSBASE REGISTRY. (29th November 2012) - Hughes, SE; Spelman, T; Gray, OM; Boz, C; Trojano, M; McDonnell, GV; Hawkins, SA; Kee, F; Butzkueven, H
Abstract : Background: Several studies have shown that pregnancy reduces relapse rate in Multiple Sclerosis (MS), followed by an increased relapse rate in the early postpartum period. We re-examined the effect of pregnancy on MS using the international MSBase Registry, examining predictors of early post-partum relapse. Methods: We performed a prospective observational multi-centre case-control study, with self-control. Annualised relapse rate (ARR) and median Expanded Disability Status Scale (EDSS) scores were compared for the 24 months pre-conception, pregnancy and 24 months postpartum periods. Clustered logistic regression was used to investigate predictors of early postpartum relapses. Results: We included 893 pregnancies in 674 females with MS. Mean ARR (SD) for 24 months pre-pregnancy was 0.32 (0.45), decreasing to 0.13 (0.77) by 3rd trimester of pregnancy. ARR rose to 0.61 (1.61) in the 1st 3 months postpartum, and returned to baseline by 24 months. Median EDSS remained stable. Higher pre-conception ARR predicted early postpartum relapse and an independent protective effect was observed with disease-modifying treatment (DMT) use in the 2 years pre-conception. Conclusion: We confirm a favourable effect of pregnancy on relapse rate in MS, strongest in the third trimester, and a peak in relapses in the early postpartum period. In the pre-conception period, DMT exposure and low ARR conferred independent protective effects for postpartum relapse. This novel finding could provide clinicians with a strategy to minimise risk of postpartum relapse in women with MS planning pregnancy.